The Calculation of the Ettingshausen Coefficient in Quantum Wells under the Influence of Confined Phonons (for Electron – confined Optical Phonon Scattering) - Thi Lam Quynh, Nguyen; Thi Vi Ba, Cao; Quang Bau, Nguyen (VNU Journal of Science: Mathematics - Physics, 2019)
Abstract: In this paper, we have used the method of quantum kinetic equation to calculate the analytic expression for Ettingshausen coefficient (EC) under the influence of confined phonon. We considered a quantum well in the presence of constant electric field, magnetic field and electromagnetic wave (EMW) with assumption that electron – confined optical phonon (OP) scattering is essential. The EC obtained depends on many quantities in a complicated way such as temperature, magnetic field, frequency or amplitude of EMW and m - quantum number which specify confined OP. Numerical results for GaAs/GaAsAl quantum well (QW) have displayed clearly the differences in comparison with both cases of bulk semiconductor and unconfined phonon. The result of examining the EC’s dependence on magnetic field shows that quantum number m changes resonance condition; m not only makes the increase in the number of resonance peak but also changes the position of peaks. When m is set to zero, we get the results that corresponds to unconfined OP. Keywords: Quantum well, Ettingshausen effect, Quantum kinetic equation, confined optical phonons. References [1] N.Q. Bau, D.T. Long, Impact of confined LO-phonons on the Hall effect in doped semiconductor supperlatices, Journal of Science: Advanced Materials and Devices 1 (2016) 209-213. [2] L.T. Hung, N.V. Nhan, N.Q. Bau, The impact of confined phonons on the nolinear obsorption coefficient of a strong electromagnetic wave by confined electrons in compositional supperlatices, VNU Journal of Science, Mathematics - Physics 28 (2012) 68-76. [3] N.Q. Bau, D.T. Long, Influence of confined optical phonons and laser radiation on the Hall effect in a compositional supperlatices, Physica B:Condensed Matter 532 (2018) 149-154. [4] N.Q. Bau, D.T. Hang, D.M. Quang, N.T.T. Nhan, Magneto-thermoelectric effect in quantum well in the presence of electromagnetic wave, VNU Journal of Science, Mathematics – Physics 32 (2017) 1-9. [5] D.T. Hang, D.T. Ha, D.T.T. Thanh, N.Q. Bau, The Ettingshausen coefficient in quantum wells under the influence of laser radiation in the case of electron-optical phonon interaction, Photonics Letters of Poland, 8 (3) (2016) 79-81. [6] B.V. Paranjape, J.S. Levinger, Theory of the Ettingshausen effect in emiconductors, Phys. Rev. 120 (1960) 437-441.